STUDYING THE LONG-TERM RELATIONSHIP BETWEEN GOVERNANCE AND ECONOMIC GROWTH DURING THE PERIOD Q1 2010-Q4 2021- A COMPARATIVE STUDY BETWEEN ALGERIA AND EGYPT - Saad Elfiki, Mohamed; Ait-Yahia, Samir; Boualleg, Noura (The journal of contemporary issues in business and government, 2024)
The study aimes at search for the relationship between governance and economic growth during the period Q12010-Q42021. The data has been converted to quarterly in order to study the relationship between the variables in the long term. Depending on (the index of effective governance, the rule of law, and administrative corruption) as independent variables, (the rate of economic growth) as a dependent variable, based on the VECM model. The results of the Johnson test showed the existence of a co-integration relationship between the indicators of good governance and economic growth, and the existence of an equilibrium relationship in the long term, while there is a unidirectional causal relationship between the governance effectiveness index and the administrative corruption index in Algeria, and the existence of a unidirectional causal relationship that goes from the effectiveness of governance towards administrative corruption in Egypt and the absence of the relationship in the opposite direction. In addition to the presence of a negative impact of each of the indicators of effectiveness of governance and administrative corruption on economic growth, and from it, the relationship between them is an inverse relationship in both Algeria and Egypt. It was also concluded that there is a positive effect of the rule of law indicator on economic growth, and from it the relationship is a positive relationship.